Discovering cooperation: Endogenous change in international organizations - Tobias Lenz; Besir Ceka; Liesbet Hooghe; Gary Marks; Alexandr Burilkov (The Review of International Organizations, 2022)
Why do some international organizations (IO) accrete delegated authority over time while in others delegation is static or declines? We hypothesize that the dynamics of delegation are shaped by an IO's founding contract. IOs rooted in an open-ended contract have the capacity to discover cooperation over time: as new problems arise these IOs can adopt new policies or strengthen collaboration in existing areas. This, in turn, triggers a demand for delegation. However, this logic is mediated by the political regime of the IO. In predominantly democratic IOs, delegation is constrained by politicization which intensifies as an IO's policy portfolio broadens. These claims are tested using an updated version of the Measure of International Authority dataset covering 41 regional IOs between 1950 and 2019. Controlling for alternative explanations and addressing potential endogeneity across a range of model specifications, we find robust support for our argument.
Keywords: 320; International organization; Regional organization; Delegation; Institutional design; Politicization; Endogenous change